Illocutionary speech acts and language style analysis of Biden's speech at the Eid Al-Fitr celebration in 2022 - Ahmad, Ahmad Ismail; Fudiyartanto, Fuad Arif (Beyond Words, 2023)
Islamic issues have always been intriguing topics to discuss, especially in the Western world, where Islam is a minority religion. It is more prominent and becomes the center of public attention when a person of political power delivers the issue. For such a reason, this paper seeks to analyze Biden's speech when hosting a reception of the Eid Al-Fitr celebration in the east room of the White House in Washington, DC, on May 2, 2022. His speech is examined through Searles illocutionary speech act and Kerafs language styles theory. A qualitative approach was applied in this study. The present study finds that according to Searles theory, Bidens speech was mostly assertive. It was because he wanted to assert Eid Al-Fitr as a sign of the end of Ramadan as well as to appreciate Muslim Americans contributions to the state. Furthermore, Biden utilizes five classifications of language styles: climax, anticlimax, parallelism, antithesis, and repetition (epizeuxis, anaphora, and anadiplosis). Consequently, by employing various language styles to emphasize important messages, Biden's speech can positively influence Muslim American citizens.